gwp 2019
DOI: 10.24149/gwp359
|View full text |Cite
|
Sign up to set email alerts
|

Ties that Bind: Estimating the Natural Rate of Interest for Small Open Economies

Abstract: This paper estimates the natural interest rate for six small open economies (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This topic is very important for several reasons: (1) Trade integration has important implications for business cycle synchronization [13,14], and there is substantial empirical evidence indicating that business cycles are more synchronized in countries with strong trade intensity [15][16][17], which provides further indication of policy coordination [18,19], one of the five priorities of the BRI; (2) Bilateral trade links have always played an important role in the overall relationship between countries. In a world economy that increasingly has a regional architecture, national developments and regional trajectories will be intertangled [20], so that countries with more intense reciprocal trade links are inclined to have fewer trade conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…This topic is very important for several reasons: (1) Trade integration has important implications for business cycle synchronization [13,14], and there is substantial empirical evidence indicating that business cycles are more synchronized in countries with strong trade intensity [15][16][17], which provides further indication of policy coordination [18,19], one of the five priorities of the BRI; (2) Bilateral trade links have always played an important role in the overall relationship between countries. In a world economy that increasingly has a regional architecture, national developments and regional trajectories will be intertangled [20], so that countries with more intense reciprocal trade links are inclined to have fewer trade conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…First, the struggles of the BOJ and ECB to achieve their mandates illustrate the difficulties in raising inflation once longer-run inflation expectations become entrenched 38 For a review of financial and macroeconomic effects in the United States and abroad, see Andrade and others (2016); Lombardi, Siklos, and St. Amand (2018); Kuttner (2018); and Dell'Ariccia, Rabanal, and Sandri (2018) on the effect on yields and bank lending. On the international experience and spillovers, see Clarida (2019b), Martínez-García (2019), and the evidence in Haldane and others (2016), Chen and others (2016), and Martínez-García (2018). communications and actions at the time also conveyed a lack of confidence in its tools and uneasiness with their deployment.…”
Section: Monetary Policy Framework?mentioning
confidence: 99%
“…8 In this paper, I build on the theoretical two-country work of Martínez-García (2019) and Clarida (2019), among others. 9 Structural estimates of the natural rate of interest motivated by New Keynesian theory do exist such as the closed-economy estimate of Cúrdia et al (2015) for the U.S. and the small-open economy estimates of Grossman et al (2019) which are shown to strongly comove with the U.S. natural rate. 10 However, I argue that the two-country setup is particularly well suited to explore the domestic and foreign sources of ‡uctuations on the U.S. natural rate (and on U.S. output potential) because it recognizes the in ‡uence that domestic conditions can have on terms of trade for large economies like the U.S. and because it explicitly incorporates potentially important trade and technological linkages between the U.S. and the rest of the world.…”
Section: Introductionmentioning
confidence: 99%